Double burden of malnutrition as a risk factor for overweight and obesity - Bernabé-Ortiz, Antonio (2022)
OBJECTIVE To assess the longitudinal effect of double burden of malnutrition (DBM) on the risk of developing child and adolescent overweight or obesity. METHODS Analysis of the Peruvian Young Lives Study, younger cohort: baseline (2002) and 4 follow-ups (2006–2007, 2009–2010, 2013–2014, and 2016–2017). Outcomes were the incidence of overweight and obesity as defined by the World Health Organization standards. The exposure comprised a variable with 4 categories: non-stunted child with a non-overweight mother (reference group), non-stunted child with an overweight mother, stunted child with a non-overweight mother, and stunted child with an overweight mother (i.e., DBM). Poisson regression models were built to assess the association of interest, and relative risks (RR) and 95%CI were reported. RESULTS Data from 2,034 children; 50.0% were girls and the mean age was 12.0 (3.6) months at baseline. Non-stunted children with an overweight mother had greater risk (RR = 1.64; 95%CI: 1.35–1.99) of developing overweight, compared with the risk for stunted children with a non-overweight mother (RR = 1.38; 95%CI: 1.10–1.72), and for those with DBM (RR = 1.28; 95%CI: 1.02–1.61). When compared with the reference group, obesity risk was greater among non-stunted children with an overweight mother (RR = 2.33; 95%CI: 1.68–3.22), greater among stunted children with a non-overweight mother (RR = 2.59; 95%CI: 1.75–3.84), and greater among those with DBM (RR = 2.14; 95%CI: 1.39–3.28). CONCLUSIONS DBM is a risk factor for childhood overweight and obesity in Peru. Dual-duty policies tackling both undernutrition in children and overweight in mothers are needed to reduce DBM and its future effects in Peru.